From Learning Psychiatry to Becoming Psychiatrists: A Qualitative Study of Co-constructive Patient Simulation - Martin, Andrés; Weller, Indigo; Amsalem, Doron; Adigun, Ayodola; Jaarsma, Debbie; Duvivier, Robbert; de Carvalho-Filho, Marco Antonio (Frontiers in Psychiatry, 2021)
Objectives Co-constructive patient simulation (CCPS) is a novel medical education approach that provides a participatory and emotionally supportive alternative to traditional supervision and training. CCPS can adapt iteratively and in real time to emergent vicissitudes and challenges faced by clinicians. We describe the first implementation of CCPS in psychiatry. Methods We co-developed clinical scripts together with child and adolescent psychiatry senior fellows and professional actors with experience performing as simulated patients (SPs). We conducted the simulation sessions with interviewers blind to the content of case scenarios enacted by the SPs. Each hour-long simulation was followed by an hour-long debriefing session with all participants. We recorded and transcribed case preparation, simulation interactions, and debriefing sessions, and analyzed anonymized transcripts by applying inductive thematic analysis within a constructivist framework, aided by NVivo software. Results Each of six CCPS sessions was attended by a median of 13 participants (range, 11 – 14). The first three sessions were conducted in person; the last three, which took place during the COVID-19 pandemic, via synchronized videoconferencing. Each of the sessions centered on clinically challenging and affectively charged situations informed by trainees’ prior experiences. Through iterative thematic analysis we derived an alliterating ‘9R’ model centered on three types of Reflection: a) in action / ‘while doing’ (Regulate, Relate and Reason); b) on action / ‘having done’ (Realities, Restraints and Relationships); and c) for action / ‘will be doing’ (with opportunities for Repair and Reaffirmation). Conclusions CCPS is an experiential approach that fosters autonomous, meaningful, and individually tailored learning opportunities. CCPS and the 9R model can be effectively applied to psychiatry and have the potential to contribute uniquely to the educational needs of its trainees and practitioners.